Human Resource Information Systems Usage and Competitiveness of Organisations: A Survey of Higher Learning Institutions in Tanzania - Mbamba , Ulingeta O.L.; Sanga , John J. (University of Dar es Salaam Library Journal, 2024)
This study mainly aimed to analyse the role of Human Resource Information Systems (HRIS) in driving organisational competitiveness of Higher Learning Institutions (HLIs) through improved human resource management (HRM). Specifically, it determined the influence of HRIS use on administrative costs, HR service delivery and HR innovation using data collected from HR managers and heads of academic and administrative departments or sections responsible for handling HR activities in the HLIs under review. Employing a quantitative survey, the study gathered data from purposively selected human resource and administrative officers in both public and private HLIs. The analysis of the data collected entailed the use of Partial Least Square Structural Equation Modelling (PLS-SEM). The results show that using HRIS reduces administrative costs, improves the quality of HR service delivery, and promotes innovation in HR service delivery. These results demonstrate that the investment and extensive use of HRIS can further enhance organisational competitiveness. This paper contributes innovatively to HRM literature by empirically demonstrating the potential benefits of HRIS in HLIs, particularly against the backdrop of scarce empirical studies that have specifically examined the direct impact of HRIS on organisational competitiveness in HLIs in the context of low-technology countries such as Tanzania.